Theoretical consideration of charge transport through the nanoindentor/GaAs junction - Kosogor, A.O.; Nowak, R.; Chrobak, D.; L’vov, V.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
The process of indentation of GaAs single crystal by the conductive nanoindentor has been analyzed theoretically. The diode formed by the nanoindentor tip and small area of GaAs platelet has been considered. The evolution of local mechanical stress during the nanoindentation cycle and an appropriate transformation of electric potential difference inherent in tip/GaAs junction are described qualitatively. The nonmonotone variation of the mechanical stress and electric potential difference during the indentation cycle has been disclosed. The current spike experimentally registered in the moment of abrupt penetration of indentor tip into the GaAs platelet has been attributed to the non-monotone variation of potential difference during the indentation cycle.